Using a multiwavelength suite of microwave instruments to investigate the microphysical structure of deep convective cores. Issue 16 (24th August 2016) - Battaglia, A.; Mroz, K.; Lang, Tim; Tridon, F.; Tanelli, S.; Tian, Lin; Heymsfield, Gerald M.
Abstract: Due to the large natural variability of its microphysical properties, the characterization of solid precipitation is a longstanding problem. Since in situ observations are unavailable in severe convective systems, innovative remote sensing retrievals are needed to extend our understanding of such systems. This study presents a novel technique able to retrieve the density, mass, and effective diameter of graupel and hail in severe convection through the combination of airborne microwave remote sensing instruments. The retrieval is applied to measure solid precipitation properties within two convective cells observed on 23–24 May 2014 over North Carolina during the IPHEx campaign by the NASA ER‐2 instrument suite. Between 30 and 40 degrees of freedom of signal are associated with the measurements, which is insufficient to provide full microphysics profiling. The measurements have the largest impact on the retrieval of ice particle sizes, followed by ice water contents. Ice densities are mainly driven by a priori assumptions, though low relative errors in ice densities suggest that in extensive regions of the convective system, only particles with densities larger than 0.4 g/cm 3 are compatible with the observations. This is in agreement with reports of large hail on the ground and with hydrometeor classification derived from ground‐based polarimetric radars observations. This work confirms that multiple scattering generated by large ice hydrometeors in deep convection is relevant for airborne radar systems already at Ku band. A fortiori, multiple scattering will play a pivotal role in such conditions also for Ku band spaceborne radars (e.g., the GPM Dual Precipitation Radar). Key Points: Novel technique to retrieve microphysics of graupel and hail in severe convection via the combination of microwave instruments Observations compatible with high‐density ice in agreement with ground reports and with polarimetric radar hydrometeor classification Multiple scattering generated by large ice hydrometeors in deep convection is relevant for airborne radar systems already at Ku band